2000
DOI: 10.1007/s004320000126
|View full text |Cite
|
Sign up to set email alerts
|

Activity of extracranial metastases as a prognostic factor influencing survival after radiosurgery of brain metastases

Abstract: Information about prognostic factors influencing survival have been only occasionally reported in studies on the use of radiosurgery in the treatment of patients with brain metastasis. To answer the question of whether activity of extracranial metastases is an independent prognostic factor influencing survival in radiosurgery of brain metastases, a review of the literature was performed. Fourteen studies were identified in the English language literature that dealt with this topic. Only three studies showed bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Extracranial metastases as a prognostic predictor have been reviewed previously. Regardless of the Recursive Partitioning Analysis (RPA) or the DS-GPA index or any other prognostic index, ECM has always been an independent prognosticator influencing survival and is most often the strongest one14-17. In our study, ECM was once again confirmed to be prognostic.…”
Section: Discussionsupporting
confidence: 57%
“…Extracranial metastases as a prognostic predictor have been reviewed previously. Regardless of the Recursive Partitioning Analysis (RPA) or the DS-GPA index or any other prognostic index, ECM has always been an independent prognosticator influencing survival and is most often the strongest one14-17. In our study, ECM was once again confirmed to be prognostic.…”
Section: Discussionsupporting
confidence: 57%
“…To prolong the survival of those patients, a vital factor that should be carefully considered and managed is the concurrence of extracranial metastasis and its activity. The presence of extracranial metastasis is known as an independent prognostic factor for the survival of patients with brain metastases [10][11][12][13]. In addition, the number of extracranial metastatic sites is negatively correlated with survival [14][15][16].…”
Section: Introductionmentioning
confidence: 99%